161213 初版 161213 更新
例1
\(\displaystyle{\int_\alpha^\beta(x-\alpha)^2dx}\)
\(=\dfrac{1}{3}(\beta-\alpha)^3\)
平行移動の原理を用いて説明します。
\(\displaystyle{\int_\alpha^\beta(x-\alpha)^2dx}\)
\(=\displaystyle{\int_0^{\beta-\alpha}x^2dx}\)
\(=\dfrac{1}{3}(\beta-\alpha)^3\)
例2
\(\displaystyle{\int_\alpha^\beta(x-\alpha)(x-\beta)dx}\)
\(=-\dfrac{1}{6}(\beta-\alpha)^3\)
平行移動の原理を用いて説明します。
\(\displaystyle{\int_\alpha^\beta(x-\alpha)(x-\beta)dx}\)
\(=\displaystyle{\int_0^{\beta-\alpha}x(x-(\beta-\alpha))dx}\)
\(=(\dfrac{1}{3}-\dfrac{1}{2})(\beta-\alpha)^3\)
\(=-\dfrac{1}{6}(\beta-\alpha)^3\)
例3
\(\displaystyle{\int_\alpha^\beta(x-\alpha)^2(x-\beta)dx}\)
\(=-\dfrac{1}{12}(\beta-\alpha)^4\)
平行移動の原理を用いて説明します。
\(\displaystyle{\int_\alpha^\beta(x-\alpha)^2(x-\beta)dx}\)
\(=\displaystyle{\int_0^{\beta-\alpha}x^2(x-(\beta-\alpha))dx}\)
\(=(\dfrac{1}{4}-\dfrac{1}{3})(\beta-\alpha)^4\)
\(=-\dfrac{1}{12}(\beta-\alpha)^4\)